AN EXAMPLE OF DOUBLE FOURIER–HAAR SERIES WITH A NONREGULAR SUBSERIES - Keryan, K.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
We bring an example of integrable function on [0;1]^2, so that the double Fourier–Haar series has a subseries, whose majorant of partial sums does not belong to L^1, ∞.